Cytochrome P450 isoforms in the Metabolism of Decursin and Decursinol Angelate from Korean Angelica - ZHANG, Jinhui (Am J Chin Med, 2015)
We have shown that the in vitro hepatic microsomal metabolism of pyranocoumarin compound decursinol angelate (DA) to decursinol (DOH) exclusively requires cytochrome P450 enzymes (CYP) whereas the conversion of its isomer decursin (D) to DOH can be mediated by CYP and esterase(s). To provide insight into specific isoforms involved, here we show with recombinant human CYP that 2C19 was the most active at metabolizing D and DA in vitro followed by 3A4. With carboxylesterases (CES), D was hydrolyzed by CES2 but not CES1, and DA was resistant to both CES1 and CES2. In human liver microsomal preparation, general CYP inhibitor 1-aminobenzotriazole (ABT) and respective competitive inhibitors for 2C19 and 3A4, (+)-N-3-benzylnirvanol and ketoconazole, substantially retarded the metabolism of DA and, to a lesser extent, of D. In healthy human subjects from a single-dose pharmacokinetic study, 2C19 extensive metabolizer genotype (2C19*17 allele) tended to have less plasma DA AUC(0–48h) and poor metabolizer genotype (2C19*2 allele) tended to have greater DA AUC(0–48h). In mice given a single dose of D/DA, pretreatment with ABT boosted the plasma and prostate levels of D and DA by more than an order of magnitude. Taken together, our findings suggest that CYP isoforms 2C19 and 3A4 may play a crucial role in the first pass liver metabolism of DA and, to a lesser extent, that of D in humans. Pharmacogenetics with respect to CYP genotypes and interactions among CYP inhibitor drugs and D/DA should therefore be considered in designing future translation studies of DA and/or D.